Development of an Information System for Coastal Tourism Industry Management in Jepara Regency - Budi Soesilo; Yudha Dwi Putra Negara; Mukhamat Ainurrindo; Khoironi Khoironi (Journal of Advanced Vocational Information and Communication Technology, 2026)
Based on the identified problems, the availability of tourism information remains suboptimal due to the rapid development of coastal tourist attractions and the increasing number of visitors. In addition, the information provided by the government through social media and official websites does not yet comprehensively present detailed and integrated information related to coastal tourism. Therefore, this study proposes the development of a system to assist visitors in selecting coastal tourist destinations according to their preferences. The system is implemented through web-based mapping of the coastal tourism industry in Jepara Regency using the Waterfall method. The proposed web-based coastal tourism industry information system provides comprehensive information on coastal tourist destinations and the related tourism industries, including visitor statistics, beach locations, entrance fees, accommodations, dining and leisure facilities, tourist attractions, as well as local micro, small, and medium enterprises (MSMEs) and their products located within the coastal areas. This system is expected to deliver accurate and complete information to potential tourists planning to visit coastal destinations in Jepara Regency.